2017
DOI: 10.1002/glia.23196
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular reorganization and altered phosphorylation of the astrocytic gap junction protein connexin43 in human and experimental temporal lobe epilepsy

Abstract: Dysfunctional astrocytes are increasingly recognized as key players in the development and progression of mesial temporal lobe epilepsy (MTLE). One of the dramatic changes astrocytes undergo in MTLE with hippocampal sclerosis (HS) is loss of gap junction coupling. To further elucidate molecular mechanism(s) underlying this alteration, we assessed expression, cellular localization and phosphorylation status of astrocytic gap junction proteins in human and experimental MTLE-HS. In addition to conventional confoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
85
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(97 citation statements)
references
References 41 publications
9
85
0
Order By: Relevance
“…This extent of coupling is in the same range as in adult rodent hippocampus (Gosejacob et al, ; Griemsmann et al, ; Wallraff et al, ). The relative contribution of Cx43 versus Cx30 to intercellular coupling was not determined in human hippocampus, but in a subsequent study, the Western blot analysis revealed similar protein expression levels of the two isoforms in man and mouse (about 10‐fold more Cx43 than Cx30 in both species; Deshpande et al, ), suggesting that coupling between astrocytes in human hippocampus is also mainly accomplished by Cx43. Coupling of astrocytes seems to be a key prerequisite for maintaining ion homeostasis and proper neuronal signaling, because its loss was suggested to cause epilepsy (Bedner et al, ).…”
Section: Functional Properties Of Human Astrocytes and Ng2 Gliamentioning
confidence: 94%
See 1 more Smart Citation
“…This extent of coupling is in the same range as in adult rodent hippocampus (Gosejacob et al, ; Griemsmann et al, ; Wallraff et al, ). The relative contribution of Cx43 versus Cx30 to intercellular coupling was not determined in human hippocampus, but in a subsequent study, the Western blot analysis revealed similar protein expression levels of the two isoforms in man and mouse (about 10‐fold more Cx43 than Cx30 in both species; Deshpande et al, ), suggesting that coupling between astrocytes in human hippocampus is also mainly accomplished by Cx43. Coupling of astrocytes seems to be a key prerequisite for maintaining ion homeostasis and proper neuronal signaling, because its loss was suggested to cause epilepsy (Bedner et al, ).…”
Section: Functional Properties Of Human Astrocytes and Ng2 Gliamentioning
confidence: 94%
“…Cx30 and Cx43 protein and transcripts are also expressed in the human (Aronica et al, 2001;Collignon et al, 2006;Deshpande et al, 2017;Elisevich, Rempel, Smith, & Edvardsen, 1997;Fonseca, Green, & Nicholson, 2002;Naus, Bechberger, & Paul, 1991). However, the presence of protein does not necessarily mean that functional channels are formed.…”
Section: Gap Junction Coupling Between Human Astrocytesmentioning
confidence: 99%
“…As just a few examples: Deshpande et al . employed ExM to probe the subcellular organization of the astrocytic gap junction protein Cx43, in human brain specimens, revealing fine details of the organization of this protein amidst blood vessels and other cell types, and how this organization changed in the context of epilepsy. Crittenden et al .…”
Section: Nanoscale Detection Of Proteins With Expansion Microscopymentioning
confidence: 99%
“…In the short time since these technologies were published, already dozens of papers have begun to appear utilizing expansion microscopy to probe the relative organizations of proteins and other biomolecules. As just a few examples: Deshpande et al [45] employed ExM to probe the subcellular organization of the astrocytic gap junction protein Cx43, in human brain specimens, revealing fine details of the organization of this protein amidst blood vessels and other cell types, and how this organization changed in the context of epilepsy. Crittenden et al [46] used expansion microscopy to resolve the arrangement of striosomal fibers and dopamine-containing dendrites in the substantia nigra, revealing the densely intertwined nature of striosomal axons and dopamine-containing dendrites.…”
mentioning
confidence: 99%
“…So far this strategy has not been applied to completely non-biological objects, but in principle it could be applied to any porous object that is amenable to the steps described above. In biology, however, it has rapidly seen adoption, with simple protocols of use emerging, 14 and with papers rapidly appearing that apply expansion microscopy to human cancer specimens, 13 the brain of the fruit fly, 15 the larval zebrafish, 12 human brain tissue, 16 planaria, 17 the pathogen Giardia lamblia, 18 and many other kinds of specimen. Expansion of human pathology specimens has even been shown to boost the performance of machine learning algorithms in early cancer detection, 13 highlighting the potential of expansion imaging to make subtle signatures of disease into highly visible features.…”
mentioning
confidence: 99%